Improving Water Conservation at Universitas Diponegoro, Indonesia - Mochamad Arief Budihardjo; Indah Sekar Arumdani; Annisa Sila Puspita; Ambariyanto Ambariyanto (Universitas Diponegoro, 2022)
It is estimated that the amount of water needed by Universitas Diponegoro will increase in the years to come. Several efforts are required to ensure the fulfillment of water needed while also considering its sustainability. There have been studies on water conservation at the industrial level. Still, limited studies have discussed this problem in Indonesia specifically at university level. Therefore, this study discusses the water conservation program at Universitas Diponegoro that might be used as a reference for other universities to address water supply problems. This study aims to discuss in depth water conservation efforts at Universitas Diponegoro. This study incorporates a descriptive-qualitative approach along with direct observation. Some programs on water supply have been implemented in Universitas Diponegoro such as conservation, treated water consumed, water recycling and water-efficiency. The existence of rainwater harvesting tanks (RWH), reservoirs, biopores, wastewater treatment plans (WWTPs) and ponds are among the efforts that have been applied at Universitas Diponegoro in order to conserve the water. To date, Universitas Diponegoro has successfully conserved more than 75% of the water, recycling about >50% of wastewater, installing about >50% of water-saving equipment, and has treated clean water into drinking water using reverse osmosis.Keyword: water, conservation, sustainability, campus